The impact of online education during the Covid-19 pandemic on the professional identity formation of medical students: A systematic scoping review. - Jonathan Zhen Liang; Donovan Kai Wei Ng; Vijayprasanth Raveendran; Mac Yu Kai Teo; Elaine Li Ying Quah; Keith Zi Yuan Chua; Jun Kiat Lua; Jasmine Lerk Juan Owyong; Andrew Vimal Vijayan; Nur Amira Binte Abdul Hamid; Ting Ting Yeoh; Eng Koon Ong; et al. (PLoS ONE)
Evolving individual, contextual, organizational, interactional and sociocultural factors have complicated efforts to shape the professional identity formation (PIF) of medical students or how they feel, act and think as professionals. However, an almost exclusive reliance on online learning during the COVID-19 pandemic offers a unique opportunity to study the elemental structures that shape PIF and the environmental factors nurturing it. We propose two independent Systematic Evidence-Based Approach guided systematic scoping reviews (SSR in SEBA)s to map accounts of online learning environment and netiquette that structure online programs. The data accrued was analysed using the clinically evidenced Krishna-Pisupati Model of Professional Identity Formation (KPM) to study the evolving concepts of professional identity. The results of each SSR in SEBA were evaluated separately with the themes and categories identified in the Split Approach combined to create richer and deeper 'themes/categories' using the Jigsaw Perspective. The 'themes/categories' from each review were combined using the Funnelling Process to create domains that guide the discussion. The 'themes/categories' identified from the 141 included full-text articles in the SSR in SEBA of online programs were the content and effects of online programs. The themes/categories identified from the 26 included articles in the SSR in SEBA of netiquette were guidelines, contributing factors, and implications. The Funnelling Process identified online programs (encapsulating the content, approach, structures and the support mechanisms); their effects; and PIF development that framed the domains guiding the discussion. This SSR in SEBA identifies the fundamental elements behind developing PIF including a structured program within a nurturing environment confined with netiquette-guided boundaries akin to a Community of Practice and the elemental aspect of a socialisation process within online programs. These findings ought to be applicable beyond online training and guide the design, support and assessment of efforts to nurture PIF.